Innate immunity in the edible ascidian Halocynthia roretzi developing soft tunic syndrome: Hemolymph can eliminate the causative flagellates and discriminate allogeneic hemocytes. Issue 127 (August 2022) - Yanagida, Tetsuya; Nakayama, Kei; Sawada, Tomoo; Honjo, Miho; Murakami, Shoko; Iida, Takaji; Hirose, Euichi; Kitamura, Shin-Ichi
Abstract: The infection of the kinetoplastid flagellate Azumiobodo hoyamushi causes soft tunic syndrome that often results in mass mortality in the aquaculture of the edible ascidian Halocynthia roretzi . In the diseased ascidian individuals, the flagellates are exclusively found in the tunic matrix that entirely cover the epidermis, and never invade into internal tissues, such as a mantle. The present study for the first time demonstrated that the ascidian blood plasma and hemolymph have an activity to agglutinate and disintegrate the flagellates, suggesting the innate immunity protects the internal tissue from the invasion of A. hoyamushi . This activity is indifferent between the healthy and the diseased individuals. Allo-specific recognition and cytotoxic reaction among ascidian hemocytes, so-called contact reaction, occur among the individuals of healthy–healthy, healthy–diseased, and diseased–diseased combination, and therefore, the hemocytes from diseased individuals still retain the allo-reactivity. Moreover, the allo-reactive combinations are not changed under the presence of the flagellates, indicating the flagellates neither suppress nor induce the effector system of the contact reaction. These results suggest that the infection of A. hoyamushi does not impair the innate immunity in the ascidian hemolymph. Highlights: Azumiobodo hoyamushi was incubated with hemolymph or blood plasma of Halocynthia roretzi. A. hoyamushi was agglutinated and disintegrated both by hemolymph and blood plasma. Innate immunity of H. roretzi protects internal tissues from invasion of A. hoyamushi.